Does company size really matter? decision-making and planning comprehensiveness in Chinese management accounting / Robert C. Rickards - Rickards, Robert C. (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
From initiation of Deng Xiaoping’s Opening Policy in 1978 to introduction of the government’s “4 + 1” model in 2014, Chinese enterprises enjoyed great latitude in developing their internal accounting. Studies undertaken during this 36-year period generally stressed the importance of company size in the adoption of management accounting techniques and tools (MATTs), albeit without controlling for rival variables’ effects. To address that shortcoming, this investigation applied regression analysis to data collected in 2013. Doing so allowed for meaningful weighting of the explanatory variables’ relative effects and reduced the possibility of spurious relationships. The analysis showed demand for future-oriented information, company size, planning comprehensiveness, and certain valuation analytics were helpful in explaining intercompany differences in MATTs-usage. However, reliance on a managerial system of planning and control as the basis for operational decisions emerged as the major factor affecting the number of MATTs employed. The results presented here comprise a benchmark against which to measure the evolution of management accounting in Southeast Asian economies transitioning to a market orientation and to evaluate the effectiveness of relevant Chinese government policies.